Groundwater: critical for sustainable development. - Villholth, Karen G.; Signs, Mia (CGIAR Research Program on Water, Land and Ecosystems, 2019)
Groundwater represents close to 99% of all unfrozen fresh water in the world. Groundwater makes up one third of all water being used, provides almost half of the world’s population with domestic water1, and is the source of almost half of the water used for irrigation worldwide.